Analysis of Prognostic Risk Factors in Children with Disorders of Consciousness Undergoing Hyperbaric Oxygen Therapy - Zhao L; Li S; Liu Y; Di Z; Li H (Journal of Multidisciplinary Healthcare)
Long Zhao, Sha Li, Yansong Liu, Zhijuan Di, Hongling Li The Second Department of Rehabilitation, The Second Hospital of Hebei Medical University, Shijiazhuang, 050000, People’s Republic of ChinaCorrespondence: Hongling Li, The Second Department of Rehabilitation, The Second Hospital of Hebei Medical University, No. 215 Heping West Road, Shijiazhuang City, Hebei Province, 050000, People’s Republic of China, Tel +86-031166002999, Email honglingli97@126.comBackground and Objective: Disorders of consciousness (DOC) are serious neurological conditions in children, often caused by brain injury, infection, or hypoxia, with limited effective treatments. Hyperbaric oxygen therapy (HBOT) has emerged as a promising adjunctive approach due to its potential to improve cerebral oxygenation and promote neural repair. However, the prognostic factors influencing treatment outcomes in pediatric DOC remain unclear. This study aimed to identify the risk factors for prognosis of children with DOC undergoing HBOT.Methods: A retrospective analysis was conducted on 255 children diagnosed with DOC who received HBOT at the Second Hospital of Hebei Medical University from January 2010 to January 2024. Clinical data, including demographic information, etiology, Glasgow Coma Scale (GCS) scores, Coma Recovery Scale-Revised (CRS-R), treatment timing, and comorbidities, were collected. According to the Glasgow Outcome Scale (GOS) score, the children were divided into poor prognosis group and good prognosis group. Logistic regression analysis was performed to identify independent risk factors for poor prognosis.Results: Age < 12 years (OR: 0.319, 95% CI: 0.113– 0.901), late timing of HBOT intervention (OR: 41.667, 95% CI: 2.122– 818.296), low HBOT frequency (OR: 0.092, 95% CI: 0.019– 0.441), low GCS score before HBOT (OR: 0.523, 95% CI: 0.362– 0.756), low CRS-R score before HBOT (OR: 0.419, 95% CI: 0.226– 0.780), and hypoxic-ischemic encephalopathy (OR: 4.885, 95% CI: 1.508– 15.826) were risk factors for poor prognosis in DOC children (P < 0.05). Low GCS score before treatment was an independent risk factor for poor prognosis in DOC children after traumatic brain injury (P < 0.05), low CRS-R score before treatment was an independent risk factor for poor prognosis in DOC children after encephalitis (P < 0.05), and late timing of HBOT, low HBOT frequency and low CRS-R score before HBOT were independent risk factors for poor prognosis in DOC children after hypoxic-ischemic encephalopathy (P < 0.05).Conclusion: This study highlights the clinical value of early HBOT intervention and baseline neurological status in predicting recovery in children with DOC. Identifying these risk factors can help optimize treatment decisions and improve long-term neurological outcomes.Keywords: hyperbaric oxygen, children, disorders of consciousness, prognosis, influencing factor